Corrigendum to “Analysis of project-based learning implementation on Indonesian language mastery of fifth-grade students.” - Anisa Anggi Febrianti; Lina Putriyanti; Sukamto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
In the original published version of this article, the corresponding author was incorrectly listed as Anisa Anggi Febrianti. The corresponding author has now been corrected to Lina Putriyanti. The authors apologize for the error. The PDF version of the article has been updated to correct the error.